Seroprevalence of Newcastle Disease Virus in Backyard Chickens at Gazipur District of Bangladesh - Hossain, MB; Islam, MZ; Bari, MS; Torab, MA; Mondal, MAH (International Journal of Natural Sciences, 2016)
A cross-sectional study was conducted to estimate the seroprevalence of Newcastle disease (ND) in backyard chickens at Gazipur district of Bangladesh. Individual serum sample was collected from clinically healthy and non-immunized backyard chickens in four randomly selected upazilla (Sreepur, Kapasia, Kaliakor and Gazipur sadar) under Gazipur district. A total of two hundred samples (50 from each upazila) were collected from October 2009 to February 2010. Haemagglutination Inhibition (HI) test was used to determine titer of antibodies against Newcastle disease virus. The mean log2 HI titer to NDV in blood sera of the study population were found 5.54, 6.25, 4.38, 5.32 and seroprevalence were 42.53%, 45.99%, 31.91%, and37.82% in Sreepur, Kapasia, Kaliakor and Gazipur sadar upazilas respectively. The overall antibody titer and seroprevalence of Newcastle disease virus was recorded 5.37 and 39.56% respectively. Further detailed study focusing on Newcastle Disease (ND) virus strain identification and improved management packages to reduce the prevalence of Newcastle Disease (ND) are recommended. International Journal of Natural Sciences (2013), 3(1-4) 22-25